The Effect of Immunosuppressive Adjuvant Kynurenine on Type 1 Diabetes Vaccine - Sun, Jing; Shi, Jiandong; Li, Jianfang; Wu, Meini; Li, Yanhan; Jia, Sengquan; Ma, Chunli; Wang, Xinyi; Li, Zhiyuan; Hu, Ningzhu; Hu, Yunzhang (Frontiers in Immunology, 2021)
Inducing antigen-specific tolerance is a promising treatment for preventing or reversing Type 1 diabetes (T1D). In contrast to a vaccine that induces immune responses against pathogens, a tolerogenic vaccine can suppress immunity against antigens causing diseases by administrating a mixture of self-antigens with an adjuvant that decreases the strength of antigen-specific response. Kynurenine (Kyn) is an endogenous substance that can inhibit the natural killer cell and T cell proliferation and promote the differentiation of naïve T cells into regulatory T cells (Treg). In this study, we evaluated the efficacy of Kyn as a novel suppressive adjuvant. Kyn was co-immunized with GAD65 phage vaccine to induce Treg cells and tolerogenic responses for prevention of T1D in NOD mouse model. Mice were subcutaneously immunized two times with 1012 pfu GAD65 phage vaccine doses mixed with 200μg of Kyn. Serum antibodies and cytokines detected by ELISA and electrochemiluminescence, respectively. Flow cytometry assay was used to analyze DC and Treg. MTS was used for the analysis of spleen lymphocyte proliferation. RNA sequencing was used to investigate mRNA and miRNA expression profiles in splenocytes. Compared to GAD65 phage Vaccine alone, co-immunization of Kyn and GAD65 phage Vaccine resulted in prevention of hyperglycemia in 60% of mice for at least one month. Further, enhance GAD65-specific Th2-like immune responses, which repairs the Th1/Th2 imbalance and increases the number of CD4+CD25+Foxp3+T cell; suppresses DC maturation and GAD65-specific T lymphocyte proliferation. Moreover, we integrated Kyn related miRNA and mRNA expression profiles obtained from the splenocyts RNA-seq which stimulated by Kyn in vitro. These data provide an important basis for understanding the mechanisms underlying Kyn as an immunosuppressive adjuvant regulated the immune response. These findings suggest that Kyn can serve as a novel and effective suppressive adjuvant for Type 1 diabetes vaccines.